Conselho Municipal de Saúde de São Paulo: o controle social nas gestões de Celso Pitta e de Marta Suplicy - Santos, Antônia Conceição dos (2012)
The goal was characterize and analyze the council strategy comparing the mandates in order to identify the relations between the Council and the Health Movement of the East Zone of São Paulo, according to the importance of this in the genesis of that, and compare the conformation and the performance of the Council during the mandates studied, pointing the respective contributions to strength or attenuate alliances and policies in favor of the guarantee of the right to universal health, conceived as a public good. It was sought the study of the two managements that represents opposite political projects in order to understand how are processed the political relations between the government and civil society in different conjunctures. The hypothesis formulated was that the public policies Councils, generally, and the Health Councils, particularly, are in principle empty spaces that can be occupied in different ways and with different contents. Under this perspective, it is understood that the Local Health Council can be constituted in an instrument of effective democratic struggle for improvements and achievements in Health Policy, but, in other hand, can be reduced to an instrument of cooptation of the society section represented in it, in prejudice of the social control. Secondly. The section of the civil society represented in the Council tend to modify the profile of the social control and the surveillance, adopting posture support and acceptance of the mandates considered popular-democratic in which politically identified, in prejudice of their autonomy. The research is qualitative character and had as methodological procedures the document, bibliographic and empiric research through the gathering of testimonies of health counselors that represent the sections of users, workers and managers. The research followed the tensions and contradictions of the Local Health Council. It intended the analysis of the Council in the agenda, and contribute to the democratic improvement of this social control mechanism